Revolutionary Egypt in the eyes of the Muslim Brotherhood : a framing analysis of Ikhwanweb - El-Nawawy, Mohammed, 1968-; Elmasry, Mohamad Hamas, 1976- (Rowman & Littlefield, 2018)
This book delves into the media strategies and ventures of the Muslim Brotherhood by studying how it has used its official English website to frame its political ideologies and its role in the 2011 Egyptian uprising.